IMPLEMENTATION OF THE DENTAL AND ORAL HEALTH CARE SERVICE MODEL FOR AUTISTIC CHILDREN - rose aini (Wealth Community Empowerment, 2024)
Background: According to the World Health Organization (WHO) in 2012, 90% of school children throughout the world experienced dental caries. The prevalence of caries in normal school-aged children in Vietnam is 87.9%, Brazil 68%, America 59%, India 58.6%, in Taiwan 37.30%, and in Indonesia 89%. Dental and oral health problems are not only experienced by school-age children with normal body conditions, but are also experienced by children with special needs. In accordance with the characteristics of autistic children, dental health education should use interesting learning methods that can produce understanding, develop imagination and provide enjoyment. One of the media that can be used in a learning method is a 3D modified puzzle.Objective: To produce a 3D modified puzzle media model as a fun learning medium for autistic children, increase parents' knowledge about cariogenic foods as companions for children and increase children's knowledge about cariogenic foods.Target audience: Semarang State SLB autistic children accompanied by their parents.Method: The method used is a combination of several activity stages including initial data collection, intervention stage and evaluation stage.Results: 1) licensing carried out on 13 August 2021, 2) field survey on 13 August 2021, 3) Preparation of work program on 20 August 2021, 4) Appreciation on 21 August 2021, 5) Distribution of props on 13 – 20 September 2021, 6) Counseling on October 1 2021 will be held online.Conclusion: The dental and oral health maintenance behavior of autistic children is greatly influenced by the role of parents and those closest to them. So before delivering material or introductions, it is necessary to approach someone the child trusts. In this case, the role of parents, caregivers and children's teachers greatly influences the material presented.